Orientational order parameter determination of the liquid crystal: 4 propyl paraethoxy phenyl cyclohexyl carboxylate by X-ray studies. (2nd July 2016) - Roy, Saswati; Mukhopadhyay, Anuradha
ABSTRACT: The compound 4 propyl paraethoxy phenyl cyclohexyl carboxylate (code name D302) is a member of a homologous series and exhibits liquid crystalline (nematic) behavior in the temperature range 48°C to 78°C. An experiment has been set up for conducting X-ray studies of liquid crystal samples at various temperatures. From X-ray studies conducted at different temperatures on D302, the apparent molecular length and inter-molecular distance and their temperature dependence have been determined. The variation of the orientational-order parameter 2 >xray has been determined from the intensities of the scanned X-ray photographs taken at different temperatures. The results have been compared with the2 >opt values obtained by us from birefringence studies.